RANKING OF CRITERIA FOR ORDER ALLOCATION IN A RUBBER GLOVE MANUFACTURING FACTORY USING ANALYTIC HIERARCHY PROCESS (AHP) (Journal of Computational Innovation and Analytics (JCIA), 2023)
Malaysia is the world’s leading producer of rubber gloves, among over 150 manufacturers worldwide. Based on current practice among the manufacturer of rubber gloves, there is no fixed guideline in planning for the orders based on various criteria as each criterion has its importance, and the orders are planned based on the real-time situation. Therefore, in this study, the criteria to be considered for order allocation to factories and their importance were determined using Analytical Hierarchical Process (AHP) technique. Six criteria, namely quality, cost, lead time, capacity, special requirement, and regulation compliance, were identified based on the literature search of past studies in the field and supported by the expert’s opinion. Later, the experts ranked the importance of each criterion using a specifically designed questionnaire employing the AHP method. The pairwise comparison matrix was consistent with a consistency ratio (CR) value of 0.0495. Thus, the six criteria by ranking top to bottom with respective weightage are quality (25.81%), cost (21.7%), lead time (20.73%), regulation compliance (16.86%), special requirement (7.86%), and capacity (7.04%). In summary, the objectives of this research have been successfully met, according to the findings, and the criteria ranking can be used as a guideline by rubber glove manufacturers in planning for order allocation.